The Influence of Consumer Perception and Promotion on Purchase Intention Through Perceived Value: A Case Study of Depok Campus Students on a Premium FMCG Brand - Tristanto, Sigit Heri; Iswati, Heni (Manunggal Halim Jaya, 2025)
This research aims to analyze the influence of consumer perception and promotion on purchase intention through perceived value. The case study focuses on the Depok campus community regarding the premium brand PT. SCM, how do consumer perception and promotion influence purchase intention directly and through perceived value? The method used in this research is causal associative using a quantitative approach. The population in this study is the entire Depok campus community of 106 respondents. Data were collected using a Likert scale questionnaire, and validity, reliability, and hypothesis testing were conducted using SmartPLS 4.0 software. The results of this study indicate that consumer perception has a positive and significant effect on purchase intention, promotion does not have a positive and significant effect on purchase intention, consumer perception has a positive and significant effect on perceived value, promotion has a positive and significant effect on perceived value, and consumer perception has a positive and significant effect on purchase intention through perceived value. Promotion has a positive and significant effect on purchase intention through perceived value. This means that hypothesis testing in this study can significantly influence the dependent variable on the independent variable through the intervening variable.